Bicarbazole-based redox-active covalent organic frameworks for ultrahigh-performance energy storage. Issue 82 (2nd October 2017) - Feng, Shi; Xu, Hong; Zhang, Chong; Chen, Yu; Zeng, Jinghui; Jiang, Donglin; Jiang, Jia-Xing
Abstract : Integration of redox-active bicarbazole units to the backbone of porous covalent organic frameworks reveals a synergistic structural effect on achieving ultrahigh-performance energy storage. Abstract : A highly redox-active building block, bicarbazole, is developed as a monomer for designing crystalline porous covalent organic frameworks and is successfully integrated to the vertices of microporous tetragonal frameworks, leading to densely aligned redox-active arrays. The frameworks with large porosity and high accessibility of the redox-active sites exhibit synergistic structural effects and ultrahigh-performance energy storage.